2014
DOI: 10.1002/jbm.b.33163
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency sonication may alter surface topography of endoprosthetic components and damage articular cartilage without eradicating biofilms completely

Abstract: Two-stage exchange arthroplasty is the current standard of care for arthroplasty-related infections. Reinfection rates up to 30% are reported, and there is significant morbidity for the patient. In cases of failure, arthrodesis or amputation may result. Ultrasonic treatment has the potential to eradicate biofilms and avoid two-stage exchange arthroplasty. Data in the specific context of arthroplasty infections is scant, and there is debate regarding optimal frequency and intensity of treatment. Surface topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
6
1
Order By: Relevance
“…In general, the average roughness of all sonicated surfaces was lower than the untreated surfaces, particularly on PT, indicating that some ablations of the surface occurred. SEM indicated that, for the most part, the original topography was maintained and was similar to the previously published results (Zhao et al 2005;Rupp et al 2006;Gittens et al 2011;Olivares-Navarrete et al 2011;Singh et al 2014). However, defects that covered about 30% of the surface were seen on SLAson.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In general, the average roughness of all sonicated surfaces was lower than the untreated surfaces, particularly on PT, indicating that some ablations of the surface occurred. SEM indicated that, for the most part, the original topography was maintained and was similar to the previously published results (Zhao et al 2005;Rupp et al 2006;Gittens et al 2011;Olivares-Navarrete et al 2011;Singh et al 2014). However, defects that covered about 30% of the surface were seen on SLAson.…”
Section: Discussionsupporting
confidence: 88%
“…This typically leaves brush marks, and studies have shown that they are no longer detectable after application of low‐frequency ultrasound on CoCr‐knee prostheses (Singh et al. ). Whether a similar mechanism was involved in the present study is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the instance of orthopedic trauma, high pressure pulse lavage as compared to low pressure pulse lavage did not decrease the rates of reoperation, and may induce further soft tissue damage . In the case of total joint arthroplasty, pulse lavage was found to reduce the biofilm signal intensity by less than 10‐fold and low‐frequency sonication was found to not only incompletely eradicate biofilms, but also increased surface roughness of implants (maximum peak to valley height) and reduce articular cartilage thickness . Because mechanical disruption is often inadequate, removal of the infected device or implant is often necessary when possible.…”
Section: Current Clinical Practicementioning
confidence: 99%